A Care-Based Model of the Physician-Patient Relationship - Breslin, Jonathan M. (My University, 2003)
The aim of this dissertation is to offer a new way of characterizing the ideal physician-patient relationship. Although several models of the physician-patient realtionship have been put forth in the literature in recent years, they have all fallen short as ideal models of the relationship. One of the problems with many of the previous models is that they have tended to focus on finding an appropriate balance between physician paternalism and patient autonomy an, in doing so, have characterized the relationship as one in which the physician is viewed as a threat to the rights and interests of the patient. The second problem with many of the models is that they focus too narrowly on decision making, ignoring other important aspects of the relationship. For instance, there is little if any discussion in the previous models of such important aspects of the physician-patient relationship as trust and communication. Nevertheless, I maintain that the models approach is the best approach to the physician-patient ethics, and so I argue for a new model of the relationship - a model that incorporates the other important facets of the relationship, is widely applicable to different physician-patient relationships, and is more collaborative than adversarial in nature. My thesis is that 'care' serves as the ideal conceptual basis for a model of the physician-patient relationship. Thus, the main task of this dissertation is to philosophically examine the concept 'care', and to apply it to the physician-patient relationship in order to develop a care-based model of that relationship.
Keywords: Philosophy; Philosophy